MODELING AND VALIDATING PERVASIVE LEARNING ACCEPTANCE IN PAKISTANI HIGHER EDUCATIONAL INSTITUTES: A UTAUT-BASED APPROACH - Sajeela Ashfaque Tago,; Ayaz Keerio,; Shahmurad Chandio,; Altaf Hussain Abro, (Spectrum of Engineering Sciences, 2025)
Pervasive learning, mobile learning, and electronic learning are advanced learning technologies that enable students to learn wherever they want, using mobile or handheld devices. This innovative technology offers flexibility and various learning mediums, helping students overcome challenges such as poor classroom facilities, cultural and religious barriers, and busy business and personal lives. This state-of-the-art, innovative technology facilitates learning wherever the desire arises. This research attempts to examine the various aspects influencing students' acceptance and utilization of new technologies, such as pervasive learning. This research broadened the existing study on UTAUT2 and created a theoretical model for the acceptance of pervasive learning. This study should facilitate learners in planning and implementing courses that seamlessly integrate technology. This research employs quantitative methodologies and gathers data through a cross-sectional survey to achieve its targeted outcomes. The entire population is 600, comprising students from four regions of Pakistan and six universities, and data from 301 topics is utilized to validate the proposed model using the new PLS approach and cluster analysis. The findings reveal that the three antecedents of behavioural intention were context awareness, self-directed learning, hedonic motivation, personal innovativeness, personal compatibility, performance expectancy, and conducive conditions (R squared variance — v2 = .528). These empirical findings show several influences that significantly affect the adoption of pervasive learning. To enhance students' adoption of ubiquitous learning and augment its practical significance, they present several theoretical advances pertinent to higher education institutions.